Current State of Evidence for Medication Treatment of Preschool Internalizing Disorders. (22nd December 2013) - Barterian, Justin A.; Rappuhn, Erin; Seif, Erin L.; Watson, Gabriel; Ham, Hannah; Carlson, John S.
Abstract : Psychotropic medications are being prescribed off-label by psychiatrists to treat preschool children diagnosed with internalizing disorders. In this review, the current state of evidence is presented for medications used to treat preschool children (ages 2–5 year olds) diagnosed with anxiety and/or depressive disorders. Eleven studies were systematically identified for this review based on a priori criteria. Overall, the available literature revealed that studies addressing the medication treatment of internalizing disorders in preschoolers are extremely limited and represent relatively weak research methodologies. Given the increasing prevalence of the use of psychotropic medications to treat preschool children and the unique challenges associated with working with this population, it is imperative that mental health practitioners are aware of the current, albeit limited, research on this practice to help make informed treatment decisions. Suggestions about how to monitor potential costs and benefits in those unique cases in which psychopharmacological treatments might be considered for young children are given. Moreover, areas of additional research for this population are discussed.